Synchronizing optical to wireless signals using a resonant tunneling diode laser diode circuit - Romeira, B.; Figueiredo, J.; Slight, T.; Wang, L.; Wasige, E.; Ironside, Charlie (2008)
We report on a wireless to optical interface consisting of a laser diode driven by resonant tunneling diode. Circuit electrical behavior and laser output are well predicted by a Liénard's driven oscillator model. ©2008 IEEE.